Post-operative complications following feminizing genitoplasty in moderate to severe genital atypia: Results from a multicenter, observational prospective cohort study. Issue 5 (October 2020) - Baskin, Avi; Wisniewski, Amy B.; Aston, Christopher E.; Austin, Paul; Chan, Yee-Ming; Cheng, Earl Y.; Diamond, David A.; Fried, Allyson; Kolon, Thomas; Lakshmanan, Yegappan; Williot, Pierre; Meyer, Sabrina; et al.
Summary: Disorders/differences of sex development (DSD) are congenital conditions in which there is atypical chromosomal, gonadal and/or phenotypic sex. While there remains controversy around the traditionally binary concept of sex, most patients with DSD are reared either male or female depending on their genetic sex, gonadal sex, genital phenotype and status of their internal genital tract. This study uses prospective data from 12 institutions across the United States that specialize in DSD care. We focused on patients raised female. Eligible patients had moderate to severe genital atypia (defined as Prader score >2), were ≤2 years of age at entry, and had no prior genitoplasty. The aim of this study is to describe early post operative complications for young patients undergoing modern approaches to feminizing genitoplasty. Of the 91 participants in the cohort, 57 (62%) were reared female. The majority had congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (n = 52), 1 had ovo-testicular syndrome, 2 had mixed gonadal dysgenesis and 2 had partial androgen insensitivity syndrome (PAIS). Of the 50 participants who received early genitoplasty, 43 (86%) had follow-up at 6–12 months post-surgery. Thirty-two participants (64%) received a clitoroplasty, 31 (62%) partial urogenital mobilization and 4 (8%) total urogenital sinus mobilization. Eighteen percent (9/50) experienced post-surgical complications with 7 (14%) being rated as Clavien-Dindo grade III. Both parents and surgeons reported improved satisfaction with genital appearance of participants following surgery compared to baseline. This information on post-operative complications associated with contemporary approaches to feminizing genitoplasty performed in young children will help guide families when making decisions about whether or not to proceed with surgery for female patients with moderate to severe genital atypia. Summary Figure River diagram of mother's cosemsis rating over time in DSD patients undergoing early feminizing genitoplasty Summary Figure